Combining Qualitative and Quantitative Data Collection and Analysis Methods in Understanding Multiple Sclerosis Fatigue Management. Issue 2 (April 2015) - Thy, Merrill J. Turpin B.Occ.; Asano, Miho; Finlayson, Marcia
Combining qualitative inquiry with quantitative frequency data in a mixed methods research approach was valuable in understanding the strategies that people with Multiple Sclerosis (MS) used to manage their fatigue. Understanding its management is important because fatigue is often described by people with MS as their most disabling symptom and can pervade all aspects of a person's life. This research aimed to identify how often people used particular fatigue management strategies and the factors that influenced their use in the context of daily life. The methodology was Qualitative Description with phenomenological overtones using convenience sampling, interviews with semi-structured and structured components, and frequencies combined with typology development. Thirty-one people with MS from Chicago, Ill and Brisbane, Queensland in Australia who experienced fatigue were interviewed and asked to sort 15 cards with common fatigue management strategies into 3 categories, indicating whether they used them regularly, sometimes or never. Frequency counts were used to identify the number of participants who placed a specific strategy in a particular category. Frequencies were used to develop a typology with which to code the qualitative data. The strategies placed most frequently in each category were: Plan / organize the day used regularly, Ask someone for help used sometimes, and Use mobility devices never used. Mixed methods research techniques enabled us to explore the participants' fatigue management in greater depth. Each data type (i.e., qualitative and quantitative data) complemented the other and led to a richer understanding than either could provide in isolation.